2018
DOI: 10.3390/en11040961
|View full text |Cite
|
Sign up to set email alerts
|

The Periodic Characteristics of China’s Economic Carbon Intensity Change and the Impacts of Economic Transformation

Abstract: Understanding the pathway of carbon emissions is an important basis for establishing a national climate strategy. In this paper, the change in China's economic carbon intensity since its accession to the World Trade Organization has been analyzed with a time series decomposition analysis method. Four phases with distinctive features are defined, and the significant fluctuations in China's economic carbon intensity after 2001 are explained in detail. From the phase-average perspective, the contributions of majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Such regions generate emissions "on behalf of" other regions and their emissions should be in fact allocated to other regions according to the consumption approach. In the case of total emission in regions, temporal analysis would be a more appropriate approach, and such approach was used in the majority of studies concerning regional dimensions of GHG emissions [20,33,39]. However, for Poland, such analyses are impossible because of the lack of data across sufficiently long time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such regions generate emissions "on behalf of" other regions and their emissions should be in fact allocated to other regions according to the consumption approach. In the case of total emission in regions, temporal analysis would be a more appropriate approach, and such approach was used in the majority of studies concerning regional dimensions of GHG emissions [20,33,39]. However, for Poland, such analyses are impossible because of the lack of data across sufficiently long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…A large part of GHG emission-related studies on households also concerned China [37,38]. Some studies included households as one of the sectors in the decomposition analysis of changes in national emissions e.g., Zhang et al [39] and Lin et al [40]. Their studies showed that households had a positive effect on the decrease in the carbon intensity of the economy.…”
Section: Research Outcomesmentioning
confidence: 99%
“…In terms of economic structure [49], there is a proportion of secondary industry (ES). In terms of urbanization level [50], there is urbanization rate (UB); In term of population size [51], there is urban population density (POP); In term of market development [52][53][54][55][56], there are industrial enterprise structure (IE), service industry level (SI), fiscal dependence (FS) and opening level (OP). Additionally, the pre-intervention carbon intensity for five years in the period 2008-2016 is designed as predictor variables.…”
Section: Data and Variable Descriptionmentioning
confidence: 99%